MASCULINIDAD HEGEMÓNICA, ROLES DE GÉNERO Y VIOLENCIA INTRAFAMILIAR EN PUEBLA-TLAXCALA, MÉXICO - Lindor, Moïse (Universidad de Costa Rica, 2023)
The objective of the article is to analyze, from the gender perspective, the incidence ofhegemonic masculinity and stereotyped gender roles in family harmony where it refers toan increase in violence during confinement by Covid-19 in the Metropolitan Area Puebla-Tlaxcala (ZMTP) as a result of the unequal distribution of domestic chores and sexism inMexico. It is a qualitative investigation where the method of telephone and descriptiveexploratorysurvey was used. At the end of the work, it shows that cultural traditions andthe normalization of male domination prevent the eradication of abuse in the home.